Impact of Regulatory Changes on Financial Market Stability in Germany - Wagner , Karl (International Journal of Modern Risk Management, 2024)
Purpose: The aim of the study was to examine the impact of regulatory changes on financial market stability in Germany. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: The impact of regulatory changes on financial market stability in Germany has been significant, contributing to a more resilient financial system. Stricter regulations, particularly after the 2008 financial crisis, have enhanced risk management practices, increased capital requirements for banks, and improved transparency in financial transactions. These measures have reduced systemic risks and bolstered investor confidence, helping to maintain market stability even during periods of economic uncertainty. However, the increased regulatory burden has also posed challenges for financial institutions, leading to higher compliance costs and adjustments in business strategies to meet new standards. Unique Contribution to Theory, Practice and Policy: Theory of financial regulation, adaptive market hypothesis (AMH) & the institutional theory may be used to anchor future studies of the impact of regulatory changes on financial market stability in Germany. Practically, financial institutions and market participants need to adapt to evolving regulatory environments with robust risk management and compliance strategies. Policymakers should ensure that regulatory frameworks are designed to promote financial stability while accommodating the needs of financial institutions.